Analysis Of The Influence Of Green Branding, Green Perceived Value And Environmental Concern On Consumer Loyalty With Green Trust Moderation Of Electric Buses In Transjakarta - Afandi, Faiz Zainol Lutji; Sihite, Janfry (International Journal Labs, 2025)
This study aims to analyze the influence of green branding, green perceived value, and environmental concern on consumer loyalty in the context of TransJakarta electric bus services, with green trust as a moderation variable. The background of this research is based on the urgency of the transition to sustainable transportation in Jakarta and the inconsistency of TransJakarta user loyalty data. This study uses a quantitative approach with a survey method of 204 respondents using TransJakarta electric bus services, as well as Structural Equation Modeling (SEM) analysis techniques based on Partial Least Squares (SmartPLS 4.0). The results of the analysis show that the three main variables, namely green branding, green perceived value, and environmental concern, have a positive and significant effect on consumer loyalty. However, of the three moderation interactions tested, only two were significant: green trust was shown to strengthen the relationship between green perceived value and environmental concern for loyalty, while green trust moderation was found to be related to green branding insignificant. These findings indicate that consumer trust in a company's environmental commitment plays an important role in reinforcing the value impact of green perception and environmental concern on loyalty, but is not enough to moderate the pre-formed perception of green brands. This research makes a theoretical contribution to the development of the Stimulus-Organism-Response (SOR) model in the context of sustainable transportation and enriches the literature on green marketing in the public service sector. From a practical perspective, these findings can be the basis for developing more targeted marketing strategies and sustainability policies to increase the retention of electric-based public transportation users in urban areas.